Effective culture conditions for the induction of pluripotent stem cells - Okada, Minoru; Oka, Masahiro; Yoneda, Yoshihiro (Biochimica et biophysica acta, 2010)
Induced pluripotent stem (iPS) cells, which are functionally comparable to embryonic stem (ES) cells, can be generated from mouse fibroblasts by expression of a defined set of transcription factors Oct4, Sox2, Klf4, and c-Myc. Since iPS cells are generated from somatic cells, they provide an invaluable source of pluripotent stem cells for cell transplantation therapy that does not present ethical problems. However, the reprogramming efficiency is extremely low, and optimal culture conditions for iPS cell derivation have not been clearly defined. To generate iPS cells efficiently, we tested 10 different culture conditions: DMEM supplemented with 15% fetal bovine serum (FBS), Knockout DMEM with 15% FBS from Invitrogen, Equitech, or HyClone, DMEM with 15% Knockout Serum Replacement (KSR), and Knockout DMEM with 10%, 15%, 20%, 25%, or 35% KSR. These media all contain 2 mM l-glutamine, 100 μM nonessential amino acids, 100 μM beta-mercaptoethanol, 1000 units ml − 1 leukemia inhibitory factor (LIF), 50 units ml − 1 penicillin, and 50 μg ml − 1 streptomycin. Medium containing Knockout DMEM with 20% KSR permits efficient induction of iPS cells from both mouse embryonic fibroblasts (MEFs) and adult tail tip fibroblasts (TTFs). Mouse iPS cells generated in the condition express ES cell marker genes such as Oct4, Sox2, Rex1, and Nanog at levels comparable to those of ES cells. Furthermore, iPS cells derived form MEFs and adult TTFs can contribute to adult chimeras. Our iPS cell induction efficiency is greater than that described in other reports. These findings provide an important catalyst for examining different culture environments for the generation of iPS cells.